An analysis of similarities and differences in the interpretation of 'Lullaby' by He Luting on the Cello and the Gehii / Michelle Subang Kedeni - Subang Kedeni, Michelle (Faculty of Music, 2017)
This study is an effort to analyse the similarities and differences in the interpretation of "Lullaby' by He Luting on the cello and the gehu. The aim is to help people, especially students, to understand how each instrument can interpret the same piece differently due to their distinctive quality even though they are almost alike, like the case of the cello and the gehu. 'Lullaby' is a 20th century Chinese repertoire. The composer, He Luting had originally composed this piece as a piano solo in ternary form, and then rearranged it for the cello. The sample of the interview for this study are musicians that has had several years of experience with the cello and the gehu. The samples involved were interviewed via email. This study was designed with a research-based approach which includes the history of both instruments up to the analysis of the piece itself. Though the design of the gehu was inspired from the cello, both instruments have differences in interpreting the same piece, besides sharing similarities. Topics like deciding the appropriate fingering positions and the understanding how the tone colour of the instruments can influence how the instruments interpret this piece did surface. However both instruments are able to interpret and perform this piece or pieces of other cultures well, with certain rearrangements and adjustments made to the piece itself or the playing technique used.